2021
DOI: 10.6026/97320630017439
|View full text |Cite
|
Sign up to set email alerts
|

D614G substitution at the hinge region enhances the stability of trimeric SARS-CoV-2 spike protein

Abstract: Mutations in the spike protein of SARS-CoV-2 are the major causes for the modulation of ongoing COVID-19 infection. Currently, the D614G substitution in the spike protein has become dominant worldwide. It is associated with higher infectivity than the ancestral (D614) variant. We demonstrate using Gaussian network model-based normal mode analysis that the D614G substitution occurs at the hinge region that facilitates domain-domain motions between receptor binding domain and S2 region of the spike protein. Comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Computer simulations and protein modeling played an important role in shaping up our understanding of the dynamics and function of SARS-CoV-2 glycoproteins [46][47][48][49][50][51][52][53][54][55][56]. The latest extensive molecular dynamics (MD) simulations and free-energy landscape mapping studies of the SARS-CoV-2 S proteins and mutants detailed conformational changes and diversity of ensembles, further supporting the notion of enhanced functional and structural plasticity of S proteins [57][58][59][60][61][62][63]. Our recent studies offered evidence that the SARS-CoV-2 spike protein can function as an allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding [64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Computer simulations and protein modeling played an important role in shaping up our understanding of the dynamics and function of SARS-CoV-2 glycoproteins [46][47][48][49][50][51][52][53][54][55][56]. The latest extensive molecular dynamics (MD) simulations and free-energy landscape mapping studies of the SARS-CoV-2 S proteins and mutants detailed conformational changes and diversity of ensembles, further supporting the notion of enhanced functional and structural plasticity of S proteins [57][58][59][60][61][62][63]. Our recent studies offered evidence that the SARS-CoV-2 spike protein can function as an allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding [64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 80%
“…The free-energy landscapes of the S protein derived from MD simulations, together with nudged elastic pathway optimization mapping of the RBD opening, revealed a specific transient allosteric pocket at the hinge region, which is located near D614 position, influences RBD dynamics [60]. The energy analysis of the S-D614 and S-G614 proteins showed that local interactions near D614 position may be energetically frustrated and become stabilized in the S-G614 mutant through strengthening the inter-protomer association between S1 and S2 regions [63].…”
Section: Introductionmentioning
confidence: 99%
“…Markov modeling characterized the dynamics of the S protein and mutational variants, predicting the increase in the open state occupancy for the D614G mutation due to the increased flexibility of the closed state and the enhanced stabilization of the open form [ 129 ]. The energy analysis of the S-D614 and S-G614 proteins in the closed and partially open conformations showed that local interactions near D614 position may be energetically frustrated and become stabilized in the S-G614 mutant through strengthening of the inter-protomer association between S1 and S2 regions [ 130 ].…”
Section: Computational Studies Of Sars-cov-2 S Protein Binding Mechan...mentioning
confidence: 99%
“…The G614 mutation has implications for the spike protein structure, as it eliminates hydrogen bonds between the protein's S1 unit and S2 units naturally present in D614. This physicochemical change increased the protein chain flexibility ( Korber et al, 2020 ), confering enhanced thermodynamic stability irrespective of conformational states and most optimal for binding host ACE-2 ( Yazhini et al, 2021 ). Therefore, it is assumed that this mutation has improved the transmission efficiency of SARS-CoV-2 ( Yazhini et al, 2021 ; Volz et al, 2021 ) by up to approximately 50%, according to Pearson et al (2021) ( Pearson et al, 2021 ), and contributed to the increase in the variants' infectivity ( Giovanetti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This physicochemical change increased the protein chain flexibility ( Korber et al, 2020 ), confering enhanced thermodynamic stability irrespective of conformational states and most optimal for binding host ACE-2 ( Yazhini et al, 2021 ). Therefore, it is assumed that this mutation has improved the transmission efficiency of SARS-CoV-2 ( Yazhini et al, 2021 ; Volz et al, 2021 ) by up to approximately 50%, according to Pearson et al (2021) ( Pearson et al, 2021 ), and contributed to the increase in the variants' infectivity ( Giovanetti et al, 2021 ). Additionally, it has been suggested that this mutation would be associated with an increase in the fatal cases rate ( Becerra-Flores and Cardozo, 2020 ), a phenomenon clearly observed after the VOCs emerging, so far.…”
Section: Introductionmentioning
confidence: 99%